Augmenting Blood Profile and Reproduction in Buffaloes of Tribal Areas of Vadodara District (Gujarat) through Appropriate Mineral Mixture Supplementation - Chaudhary, RK; Patel, DC (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
An on-farm trial for 90 days was conducted using 20 anestrus and 20 repeat breeder buffaloes to evaluate the effect of supplementing appropriate mineral mixtures (AMMs) on their nutrient intake, blood profile, estrus occurrence, and conception. Both anestrus and repeat breeder buffaloes were randomly allotted to 2 treatments, i.e., T1 (Ionic mineral mixture) and T2 (T1 + 25% extra zinc in the chelate form). The average intake of DCP, TDN, and copper in anestrus and repeat breeder buffaloes calculated as per information collected from farmers were almost the same among treatments and as per requirements of animals. The average intake of calcium and phosphorus was higher by 65% and 45% than the requirements in anestrus and repeat breeder buffaloes. However, Zn intake was lower by about 35% of the requirement in all treatments. Blood glucose, serum total protein, and serum albumin levels increased marginally on supplementation of T1 and T2 mineral mixtures for 90 days, particularly in anestrus buffaloes. The serum triglycerides and total cholesterol increased, but non-significantly (p >0.05), particularly in T1 groups of both anestrus and repeat breeder animals, whereas levels of BUN and creatinine increased significantly (p <0.05) in both the groups of repeat breeders and T1 group of anestrus buffaloes. Activities of serum alkaline phosphatase decreased non-significantly, whereas those of alanine and aspartate aminotransferases remained mostly unaltered. In contrast, the serum Ca, P, Mg, Na, K, and Zn concentration increased significantly (p<0.05; p<0.01) following 90 days supplementation of T1 and T2 minerals in both anestrus and repeat breeders. The number of days taken for return to the heat of anestrus and repeat breeder buffaloes as well as the cost of feeding was reduced upon supplementation of T2 as compared to T1 mineral mixture. The study showed the beneficial role of mineral supplementation in improving the health and reproductive status of infertile buffaloes.